Contradiction and Paradoxes in J. M. Coetzee’s Disgrace - Sharma, Khum Prasad (Literary Studies, 2016)
J.M Coetzee’s Disgrace is a portrayal of characters in a social context of South Africa where the writer himself was brought up. It throws light on the new social milieu of post apartheid society where Lucy, a white is raped by a black African. She seems to accept this heinous deed with an ease by giving it a historical blend. She understands her rape as a black’s way of taking revenge for what whites have treated the blacks in the past. She considers it different from the universal concept of rape as a forceful sex. By making the blacks raping the white woman, Coetzee seems to be rewriting the African history and in this he dismantles the black/white dichotomy. So, I contend to carry out that Disgrace being a highly paradoxical and contradictory novel presents a world dying without hope and fear. It exposes the intellectual insecurity in South Africa which proves to be a threat to white man’s stability and culture.